2010
DOI: 10.2337/diaspect.23.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Depression Among Adults With Diabetes: Prevalence, Impact, and Treatment Options

Abstract: In Brief Patients with type 1 or type 2 diabetes are two times more likely to experience depression than their peers without diabetes. Comorbid depression results in deleterious effects on glycemic control, worsened diabetes complications, functional disability, and premature mortality. Once identified, depression can be effectively treated with antidepressant medications, psychotherapy, or a combination of both. Patients and providers should monitor depressive symptoms to identify their recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 37 publications
2
35
0
1
Order By: Relevance
“…In this study, forty one out of fifty (82%) diabetics were found to have depression based on the HADS scale. Whereas according to a meta-analysis conducted by Anderson RJ et al 13 and DeGroot M et al 14 , the prevalence of major depression among adults with diabetes was found to be 11% and clinically relevant depression was 31% respectively.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, forty one out of fifty (82%) diabetics were found to have depression based on the HADS scale. Whereas according to a meta-analysis conducted by Anderson RJ et al 13 and DeGroot M et al 14 , the prevalence of major depression among adults with diabetes was found to be 11% and clinically relevant depression was 31% respectively.…”
Section: Discussionmentioning
confidence: 95%
“…During the last 30 years, increasing evidence has shown that depression is an important comorbidity related to diabetes, 19 and that the combination of these diseases seems to affect the clinical management of T2DM. Ciechanowski et al 4 noted that the number of individuals with glycated hemoglobin levels greater than 8% was higher among the depressed.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3] Diabetes mellitus requiring lifelong management. [4] Diabetes management could deliver maximum results when coupled with client adherence to therapy is recommended by health professionals. Research conducted by reference [5] about the compliance of patients with DM in diet and physical activity, showed that 64.4% of patients with DM was not better adherence to regular physical activity and 63.3% of people with diabetes do not obey the diet.…”
Section: Introductionmentioning
confidence: 99%